Political confidence of the Parliament of the Kurdistan Region of Iraq - صالح عمر عيسى; بارزان جوهر صادق (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
ority, thus citizen’s trust in system units is significant. Governance in Kurdistan Region -Iraq has passed a quarter of century. According to scholars, after this period, political trust could be measured in each unit of political system. Some political accidents through this era have been effect on declining of political trust in Kurdistan Parliament. The Research analyzed those two variables in first chapter. In the second chapter, except of showing method and statistical mechanisms, it focuses on the analyze field data and interviews. After all, discussion on the conclusions and suggestions of the research outcomes. Outcomes show that Kurdistan people have a little trust in parliament. Day after elections, instead of society interests, members of parliament are going to gotten their political party and his interests. Statistical data and interview outcomes say that there is no opposition political parties in parliament and the hegemony of political parties on parliament in one hand and unable of parliament in observing government in other hand are become people have little trust in parliament. The research is suggested to reconstruction of political trust from beginning of s o c i a l i z a t i o n process. On the other hand, government has to concern measurement of political trust and add yearly conference to find reasons of political trust decline and how rise up. In the same time, members of parliament should work to public interests. It needs of close observation on the media and ending up the disinformation and offensiveness because it has big challenge on political trust.